Maastrichtian heteromorph ammonites from the Carnarvon Basin, Western Australia - Henderson, R; Kennedy, W; McNamara, K (1992)
A comprehensive taxonomic revision of heteromorph ammonites from the Miria Formation and the uppermost horizon, a nodule bed, of the Korojon Calcarenite is presented, with major rationalisation of earlier nomenclature and new data on the faunal sequence. Eubaculites is present throughout the succession as three biostratigraphically discrete species and Nostoceras, represented by two species, is restricted to the nodule bed. Remaining elements of the heteromorph fauna are known only from the upper part of the Miria Formation. Preservation of ammonites has been strongly influenced by taphonomic factors. Ammonites from the upper Miria Formation are of late Maastrichtian age whereas those from the nodule bed are ascribed to the early Maastrichtian. -from Authors